Successful coaching - Martens, Rainer (Human Kinetics, 1997)
Includes chapters by Brian J. Sharkey on: Principles of training; Fitness for sport; Developing your training program, and Nutrition for athletes.
Keywords: Entraînement (Sports); Schoolsport; Sports scolaires - Entraînement - États-Unis; Sporttraining; School sports -- Coaching -- United States; Trainingslehre; USA